Translanguaging dan Pembentukan Identitas Akademik Mahasiswa Multibahasa dalam Pembelajaran Bahasa Indonesia di Perguruan Tinggi - Helena Septiana Hinadang; Vivi Ajia; Nurjihad Nurjihad; Nola Julianti Kasma Putri; Jahrudin Jahrudin; Yeremias Bardi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2026)
Students in multilingual higher education contexts often face linguistic and identity challenges when engaging with formal and normative academic Indonesian. In such settings, translanguaging emerges as a natural and strategic practice that allows students to draw on their full linguistic repertoires, including local languages, to construct meaning and negotiate academic understanding. This study aims to examine students’ translanguaging practices and their contribution to the formation of academic identity in Indonesian language learning at the university level. Employing a qualitative case study design, data were collected through classroom observations, in-depth interviews with students and lecturers, and document analysis of learning materials and students’ academic assignments. The findings reveal that translanguaging functions as both a cognitive and affective strategy that facilitates conceptual understanding, enhances participation, and strengthens students’ academic confidence. Moreover, translanguaging plays a crucial role in shaping an inclusive and hybrid academic identity, positioning local languages as legitimate pedagogical resources rather than obstacles. These findings highlight the need to recognize translanguaging within language policy and curriculum design to support equitable and context-sensitive academic learning in multilingual higher education.